Roadside safety recovery zone corridor widths derived from live field experiments and comparison to past accidents records - Kunji, Ahmad Kamal; Kusbiantoro, Andri; Zulkiple, Adnan; Ramli, Harzah M (Penerbit Universiti Malaysia Pahang, 2018)
The increasing number of run-off-road accidents has driven institutions to study and introduce roadside geometric design guidelines to reduce the number of fatalities and severe injuries. Providing the right configuration and dimensions of a roadside slope cross section would allow travel lane motorists who have strayed off the travel lane with a safe way of traversing back into driving lanes and can reduce run-off-road fatal accidents or severe injuries. American Association of Highway and Transportation Official (AASHTO) introduced roadside safety clear zone derived from a set of past accident records. Unfortunately, most of other countries do not keep the same past accident records. Alternatively, safety clear zone can be derived from live field experiments. The 180 live field experiments were safely performed by five drivers with three motorcars at ten locations having various roadside slope gradients and ground surface conditions. The motorcar tires’ printed marks on the turfed roadside were measured, recorded, and analyzed to establish a safety clear zone corridor size. Comparatively, the American figures are higher as they have accounted for additional widths of nonrecovery zone and turn out area, the justifiable difference confirms that deriving roadside safety recovery zone corridor widths by the method of live field experiments is a sound engineering practice. The study concludes that the live field experiment method can be applied in place of past accident records in establishing the size of roadside safety clear zones.